Effects of culture media on metabolic profiling of the human gastric cancer cell line SGC79011. Issue 7 (16th July 2015) - Huang, Zicheng; Shao, Wei; Gu, Jinping; Hu, Xiaomin; Shi, Yuanzhi; Xu, Wenqi; Huang, Caihua; Lin, Donghai
<x xml:space="preserve">Abstract</x> Culture media significantly affect cellular metabolic profiling.